PEDAGOGICAL AND PSYCHOLOGICAL POSSIBILITIES OF PAINTINGS IN DEVELOPING AESTHETIC CULTURE IN YOUTH - Yunusaliev Mukhamadkodir Tadjimadovich (Modern American Journals, 2025)
This article analyzes the role of painting in the aesthetic education of young people, its pedagogical and psychological aspects in the formation of their taste, imagination and emotions. The influence of the harmony of color and form on the human psyche, the role of painting in developing the skills of perceiving and appreciating beauty are substantiated. Analytical thoughts on ways to effectively use painting as a means of aesthetic education in schools and secondary specialized educational institutions.
Keywords: Pedagogical process, visual activity, visual image, styles of expression, architecture, aesthetic appreciation, visual perception, creative thinking, empathy, aesthetic literacy, puzzles and visual games, mind mapping